ANALYSIS STRATEGY OF TOURISM DEVELOPMENT AT KALIBIRU, KULON PROGO AS A LEADING TOURIST ATTRACCTION IN YOGYAKARTA SPECIAL REGION - Isdarmanto, Isdarmanto (Kepariwisataan: Jurnal Ilmiah, 2016)
Tourist destinations of Kalibiru were potential to be developed as currently a moderate selection (trend), especially Tourists teens to do outbound activities and events familiarity. Considering to the location and the presence of its natural attractions which are very beautiful backed by Sermo Reservoir and the Menoreh mountains scenery was really beautiful views look from the observation post above the trees. Facilities are quite favorable by tracking through the forest area of Sermo reservoir that has unique flora and fauna. However, the management is still done by the local communities who have not been professional yet. Problems tourism development at Kalibiru until now there has been no serious research, so that the management is not optimal and constraint means the path to the location is still a bottleneck. Qualitative research methods to get the results more tangible and effective to be evaluated considering the variable conditions are very diverse. The results of the study are expected to provide enlightenment to Local Community Mandiri travel managers to be more innovative and creative and professional to understand the potential of the existing nature and able to make a strategic step how sustainable tourism development at Kalibiru nature in order to become a tourism icon in Kulon Progo region. Improving community and empowerment for managers to manage tourist destinations at Kalibiru for better in the future, and able to provide service and guarantee satisfaction to all travelers. Keywords: Tourism Destinations, Sustainable development